(untitled) - Nguyễn, Văn Thành (Proefschrift, 2004)
Content: introduction; characterization of viability and physiological state transitions of Rhizopus oligosporus; protein profiles of dormant and activated sporangiospores.
Keywords: Cell physiology,Fungi,Sinh lý học tế bào,Rhizopus oligosporus